Is There a Change in Electroconvulsive Therapy Practice Following the New Mental Health Act 2014 in Victoria?: A Study at a Metropolitan Mental Health Service. Issue 4 (December 2019) - Das, Partha; Jagadheesan, Karuppiah; Walker, Frances; Lakra, Vinay; Lautenschlager, Nicola T.; Ferraro, Angelo; Rudolph, Devapriya
Abstract : Objectives: The main objective of our study was to examine whether there has been any change to electroconvulsive therapy (ECT) practice since the new Mental Health Act 2014 (MHA) in a public metropolitan mental health service in Victoria. Methods: This retrospective study examined any change in ECT rate following the new MHA. We compared sociodemographic, clinical, and ECT-related variables for patients treated before (July 1, 2013, and June 30, 2014) and after (1st July 2014 and the 30th June 2015) the new MHA. Results: A reduction of 11.15% in ECT use per 1000 admissions and 16.4% in ECT use per 100, 000 persons was observed subsequent to the new MHA. Hospital legal status at admission positively predicted the chance of starting ECT treatment under involuntary consent. Hospital legal status at admission and discharge, history of involuntary ECT, and final Clinical Global Impression–Severity scores positively predicted, but the year of treatment negatively predicted the chance of completing ECT treatment under involuntary consent. Conclusions: The new MHA appeared to have been associated with reduced ECT use and lower rate of completing ECT under involuntary consent.